Pharmacokinetic interactions between primaquine and pyronaridine-artesunate in healthy adult Thai subjects. - Jittamala, P; Pukrittayakamee, S; Ashley, E; Nosten, F; Hanboonkunupakarn, B; Lee, S; Thana, P; Chairat, K; Blessborn, D; Panapipat, S; White, N; Day, N; et al. (American Society for Microbiology, 2015)
Pyronaridine-artesunate is a newly introduced artemisinin-based combination treatment which may be deployed together with primaquine. A single-dose, randomized, three-sequence crossover study was conducted in healthy Thai volunteers to characterize potential pharmacokinetic interactions between these drugs. Seventeen healthy adults received a single oral dose of primaquine alone (30 mg base) and were then randomized to receive pyronaridine-artesunate alone (540-180 mg) or pyronaridine-artesunate plus primaquine in combination, with intervening washout periods between all treatments. The pharmacokinetic properties of primaquine, its metabolite carboxyprimaquine, artesunate, its metabolite dihydroartemisinin, and pyronaridine were assessed in 15 subjects using a noncompartmental approach followed by a bioequivalence evaluation. All drugs were well tolerated. The single oral dose of primaquine did not result in any clinically relevant pharmacokinetic alterations to pyronaridine, artesunate, or dihydroartemisinin exposures. There were significantly higher primaquine maximum plasma drug concentrations (geometric mean ratio, 30%; 90% confidence interval [CI], 17% to 46%) and total exposures (15%; 6.4% to 24%) during coadministration with pyronaridine-artesunate than when primaquine was given alone. Pyronaridine, like chloroquine and piperaquine, increases plasma primaquine concentrations. (This study has been registered at ClinicalTrials.gov under registration no. NCT01552330.).